2014
DOI: 10.1590/rou.2014.014
|View full text |Cite
|
Sign up to set email alerts
|

Oral health care: the knowledge and work of the community health agent

Abstract: ResumoIntrodução: Com a reorganização da política de saúde bucal em 2004, o agente comunitário de saúde passa a ser considerado como um facilitador das ações de saúde bucal em sua área de atuação. Objetivo: Identificar conhecimento e prática do agente comunitário de saúde sobre atenção em saúde bucal. Material e método: Este estudo é uma pesquisa qualitativa baseada na Teoria das Representações sociais, cujos dados foram coletados através de entrevista semi-estruturada, tendo como técnica de tabulação e anális… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…20 In addition, there was uncertainty and lack of preparedness on the functions they were expected to perform. 21 Intensive training that involves practical sessions and continuous follow up has been shown to be successful in Kenya for increasing CHW's knowledge, identification and referrals of oral HIV lesions of community members. 22 Literature has shown that CHWs potentially have a vital role to play in the promotion of good oral health and prevention of oral health diseases as they form a key link between communities and the health system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 In addition, there was uncertainty and lack of preparedness on the functions they were expected to perform. 21 Intensive training that involves practical sessions and continuous follow up has been shown to be successful in Kenya for increasing CHW's knowledge, identification and referrals of oral HIV lesions of community members. 22 Literature has shown that CHWs potentially have a vital role to play in the promotion of good oral health and prevention of oral health diseases as they form a key link between communities and the health system.…”
Section: Discussionmentioning
confidence: 99%
“…22 Literature has shown that CHWs potentially have a vital role to play in the promotion of good oral health and prevention of oral health diseases as they form a key link between communities and the health system. 21 However, the study reflected our participants to be ill prepared to contribute to oral health and that their role and participation is generally poorly defined. 23 It is therefore recommended that CHWs should be exposed to regular training as a way of Continuous Professional Development (CPD).…”
Section: Discussionmentioning
confidence: 99%
“…Apesar da existência de experiências exitosas quanto à capacitação e desenvolvimento de ações de saúde bucal por ACS, há diversas pesquisas [14][15][16][17][18][19] que avaliaram os conhecimentos sobre saúde bucal pelos ACS e demonstraram lacunas de conhecimentos e necessidade de capacitação para que atuem como profissionais capazes exercer vigilância à saúde bucal. A saúde bucal, parte integrante da saúde geral dos indivíduos, configura-se de primordial relevância para que os agentes de saúde dominem seus conhecimentos básicos visando à promoção, prevenção e recuperação na microárea de atuação 19 .…”
Section: Discussionunclassified
“…Community health workers (CHWs) play a vital role in the proper function and stability of the healthcare system, especially in rural areas and act as a link between the community and the healthcare system by providing easier access to the healthcare system and disseminating scienti c knowledge within the society. [3,4] The CHW Programme launched in India in 1977, was later reformed to the National Rural Health Mission (NRHM) program in 2005 under the health department of the Government of India. [5] Initially, Auxiliary Nurse-Midwife (ANM) system was created to work at the sub-center.…”
Section: Introductionmentioning
confidence: 99%